Representações sociais de familiares sobre o atendimento das emergências psiquiátricas - Soares, Francisco Rafael Ribeiro (2014)
The reformist movements in the field of mental health have pointed battle flags, among which the prioritization of production of mental health care out of the asylum environment should be highlighted, aiming the reduction of psychiatric beds, greater control over the hospitalization, family co-participation and the rescue of the citizenship of the social players involved. With the progressive reduction of asylum beds, associated with a lot of structural problems in the health services, the occurrence of crises outside the hospital environment has been increasingly frequent, thus giving the family an important therapeutic role. In face of this scenario, there is an urgent need to understand the social construction of the care for psychiatric emergencies, identifying the meanings assigned by family members to their constituent aspects. This study seeks to answer the following research question: what are the social representations of family members about the care of psychiatric emergencies in the city of Mossoró, Rio Grande do Norte? Therefore, the aim is to analyze the social representations of family members about the care of psychiatric emergencies in the city of Mossoró, Rio Grande do Norte. This is an exploratory and descriptive study, with a mixed approach, making use of multimethods: for collection, the semi-structured interview and the Technique of Free Association of Words; for data analysis, the Thematic Analysis of Bardin and its steps was used, with the informational support of the softwares ALCESTE (Analyse Lexicale par Contexte d'un Ensemble de Segments de Texte) and Iramuteq (Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires); and the theoretical support of social representations. The study participants totaled 72, and they were selected from the following criteria: older than18 years, with degree of kinship with users suffering from some mental and behavioral disorder, and who have already witnessed a situation of crisis, rescued by the SAMU or other means and taken to the psychiatric hospital or general emergency room. Preliminary results point out: 1.Previous note of the research project with the aim to disseminate it in the scientific community and ensure the intellectual property of the work; 2.The contextual analysis of the care for emergencies in the study place. Reflection about the phenomenon provide a name to the care for the psychiatric emergencies, which is called immediate context; the technical and operational aspects that influence the care, as a specific/ general context; and mental health policies in Brazil are identified as metacontext; 3. The systematic review from randomized clinical trials in the databases PubMed, COCHRANE, LILACS, SciELO and SCIRUS, with the use of the descriptors: ‘Physical restraint’, ‘Psychiatric emergency services’, ‘Restraint’, ‘Physical and Emergency Services’, ‘Psychiatric’. Only one work met the search protocol criteria: a short-term essay that records limited results about the proportion of people who are in restraint and seclusion. It does not show statistically significant results in relation to indications, contraindications and risks of the use of physical restraint; 4. The social representations of the care for psychiatric emergencies. The study results point to the presence of five thematic categories: 1. feeling in the face of the crisis/care; 2. thoughts and perspectives about the crisis/care; 3. centrality of care in the medical- medication-hospitalization triad; 4. the thinking/acting in the face of the use of physical restraint and police force; 5. periodicity of crises. The central core of the representation is in the first category, whilst the peripheral elements are in the third and fifth categories. The contrast zone is in the second and fourth categories. The sadness is the most prominent element of the structure. The social representations about the care for psychiatric crises are at a time of transition between the hegemonic and reformist models, with the traditional aspects being predominant, but already showing peripheral and contrast elements that point to a possible change in the representational field.